GAMBARAN PERAN ORANG TUA DALAM MEMBERIKAN PENDIDIKAN SEKSUAL PADA ANAK USIA SEKOLAH DI WILAYAH KECAMATAN TAMPAN KOTA PEKANBARU: Gambaran Peran Orang Tua Dalam Memberikan Pendidikan Seksual Pada Anak Usia Sekolah Di Wilayah KecamatanTampan Kota Pekanbaru - Annovika Putra; Rani Lisa Indra; T. Abdur Rasyid (Jurnal Ilmu Keperawatan, 2019)
School-aged children are a time when children acquire the basic knowledge to acquire certain skills toward adult life. The child is a weak creature and very vulnerable to be a victims of violence, one of them sexual violence. therefore it is necessary parent role to provide sexual education to children so that sexual violence in children can be prevented. This study aimed to determine the description of the parent’s role (father and mother) in providing sexual education at school-aged children in the sub-district of Tampan in Pekanbaru City. This research used quantitative research with descriptive design. Population in this research was all of parents who have school age children with the number of samples as much as 580 people (290 for mother and 290 for father) taken by using Stratified Random Sampling technique. The data collection tool used questionnaires. Data analysis by using univariate analysis. The results showed that more fathers had less role in providing sexual education to children as many as 190 people (65.5%) while more mothers had good role as many as 175 people (60.3%). This research suggests that parents, especially fathers can increase their role in providing sexual education to children so that children avoid from sexual violence.